European guidelines for sclerotherapy in chronic venous disorders - Rabe, E.; Breu, F.; Cavezzi, A.; Smith, P.; Frullini, A.; Gillet, J.; Guex, J.; Hamel-Desnos, C.; Kern, P.; Partsch, B.; Ramelet, Anne-Sylvie; Tessari, L.; et al. (SAGE Publications Ltd, 2014)
Aim: Sclerotherapy is the targeted chemical ablation of varicose veins by intravenous injection of a liquid or foamed sclerosing drug. The treated veins may be intradermal, subcutaneous, and/or transfascial as well as superficial and deep in venous malformations. The aim of this guideline is to give evidence-based recommendations for liquid and foam sclerotherapy. Methods: This guideline was drafted on behalf of 23 European Phlebological Societies during a Guideline Conference on 7-10 May 2012 in Mainz. The conference was organized by the German Society of Phlebology. These guidelines review the present state of knowledge as reflected in published medical literature. The regulatory situation of sclerosant drugs differs from country to country but this has not been considered in this document. The recommendations of this guideline are graded according to the American College of Chest Physicians Task Force recommendations on Grading Strength of Recommendations and Quality of Evidence in Clinical Guidelines. Results: This guideline focuses on the two sclerosing drugs which are licensed in the majority of the European countries, polidocanol and sodium tetradecyl sulphate. Other sclerosants are not discussed in detail. The guideline gives recommendations concerning indications, contraindications, side-effects, concentrations, volumes, technique and efficacy of liquid and foam sclerotherapy of varicose veins and venous malformations.